The multilingual soil profile database ( SDBm Plus) (Food and Agriculture Organization of the United Nations, 2003)
This database can be used in soil monitoring and evaluation regardless of scale (regional national or local), and especially to implement tools on choosing optimal land use and management decisions in sustainable agriculture development.